Altered bladder‐related brain network in multiple sclerosis women with voiding dysfunction. Issue 7 (17th July 2022) - Shi, Zhaoyue; Karmonik, Christof; Soltes, Amelia; Tran, Khue; Lincoln, John A.; Boone, Timothy; Khavari, Rose
Abstract: Objectives: A number of neurourology imaging studies have mainly focused on investigating the brain activations during micturition in healthy and neuropathic patients. It is, however, also necessary to study brain functional connectivity (FC) within bladder‐related regions to understand the brain organization during the execution of bladder function. This study aims to identify the altered brain network associated with bladder function in multiple sclerosis (MS) women with voiding dysfunction through comparisons with healthy subjects via concurrent urodynamic study (UDS)/functional magnetic resonance imaging (fMRI). Materials and Methods: Ten healthy adult women and nine adult ambulatory women with clinically stable MS for ≥6 months and symptomatic voiding phase neurogenic lower urinary tract dysfunction (NLUTD) underwent UDS/fMRI evaluation with a task of bladder filling/emptying that was repeated three to five times. We quantitatively compared their FC within 17 bladder‐related brain regions during two UDS phases: "strong desire to void" and "(attempt at) voiding initiation." Results: At "strong desire to void, " the healthy group showed significantly stronger FC in regions involved in bladder filling and suppression of voiding compared to the patient group. These regions included the bilateral anterior cingulate cortex, right supplementary motor area, and right middle frontal gyrus. During "(attempt at) voiding initiation, " healthy subjects exhibited stronger FC in the right inferior frontal gyrus compared to MS patients. Conclusion: Our study offers a new way to identify alterations in the neural mechanisms underlying NLUTD and provides potential targets for clinical interventions (such as cortical neuromodulation) aimed at restoring bladder functions in MS patients.